Document de procédure technique pour le transfert de la gestion de la Communauté de Pratique (CoP) - Diallo, Abdoulaye Moussa; Worou, Nadine; Kane, Khady; Houessionon, Prosper; Thiaw, Moussa; Diedhiou, Lamine; Wane, Abdrahmane (International Livestock Research Institute, 2024)
The document presents the gradual transfer of management of the Community of Practice (CoP) created by AICCRA-Senegal to the Direction de l'Élevage (DIREL). The CoP brings together various public, private and community stakeholders to provide agro-climatic advice to agro-pastoralists, promoting climate-smart agriculture. An evaluation confirmed DIREL as a legitimate structure for sustaining this initiative, thanks to its organisational capacity and existing systems. Discussions led to a three-phase transfer plan: logistics, scientific organisation and financial transfer, with initial support from AICCRA. The CoP, recognised for its role in decompartmentalising institutions and disseminating reliable information, is facing challenges such as disengagement due to partially met expectations or uncertainties during a period of transition. To strengthen its impact, a merger with DIREL's Comité Pastoral (CP) is envisaged, incorporating tools to automate advice and a broader framework for collaboration between common and separate actors. This approach aims to maximise the dissemination of agro-climatic advice while reducing costs and ensuring the sustainability of activities after the withdrawal of the AICCRA project.